Vector preference and heterogeneity in host sex ratio can affect pathogen spread in natural plant populations. Issue 3 (18th January 2021) - Bruns, Emily; Pierce, Laura; Antonovics, Janis; Hood, Michael
Abstract: Vector‐borne diseases threaten human and agricultural health and are a critical component of the ecology of plants and animals. While previous studies have shown that pathogen spread can be affected by vector preferences for host infection status, less attention has been paid to vector preference for host sex, despite abundant evidence of sex‐specific variation in disease burden. We investigated vector preference for host infection status and sex in the sterilizing "anther‐smut" pathogen ( Microbotryum ) of the alpine carnation, Dianthus pavonius . The pathogen is transferred among hosts by pollinators that visit infected flowers and become contaminated with spores produced by infected anthers. The host plant has a mixed breeding system with hermaphrodites and females. In experimental floral arrays, pollinators strongly preferred healthy hermaphrodites over both females and diseased plants, consistently across different guilds of pollinators and over multiple years. Using an agent‐based model, we showed that pollinator preferences for sex can affect pathogen spread in populations with variable sex ratios, even if there is no preference for infection status. Our results demonstrate that vector preferences for host traits other than infection status can play a critical role in pathogen transmission dynamics when there is heterogeneity for those traits in the host population.